Molecular detection and characterization of vector-borne agents in common opossums (Didelphis marsupialis) from northeastern Brazil - Braga, Maria do Socorro Costa Oliveira; Costa, Francisco Borges; Calchi, Ana Cláudia [UNESP]; de Mello, Victória Valente Califre [UNESP]; Mongruel, Anna Claudia Baumel [UNESP]; Dias, Clara Morato [UNESP]; Bassini-Silva, Ricardo [UNESP]; Silva, Ellainy Maria Conceição; Pereira, José Gomes; Ribeiro, Larissa Sarmento dos Santos; da Costa, Andréa Pereira; de Andrade, Fabio Henrique Evangelista; et al. (Elsevier, 2023)
Opossums are synanthropic marsupials able to interchange among wild, peri‑urban and urban environments, playing an epidemiologically important role as hosts for emerging pathogens and ectoparasites of relevance in public health. The present study aimed to detect and molecularly characterize vector-borne agents in a population of common opossums (Didelphis marsupialis) from the Island of São Luís do Maranhão, northeastern Brazil. Of the 45 animals analyzed, one (2.22%) was positive in the nested PCR assay based on the 18S rRNA gene of piroplasmids. The obtained sequence was phylogenetically positioned in a clade containing sequences of Babesia sp. previously detected in Didelphis aurita, Didelphis albiventris and associated ticks from Brazil. Eight (17.77%) samples were positive in PCR for Ehrlichia spp. based on the dsb gene; four samples were sequenced and positioned into a new clade, sister to E. minasensis and Ehrlichia sp. clade detected in Superorder Xenarthra mammals. No samples tested positive in the screening PCR assays based on the 16S rRNA gene of Anaplasma spp. Two samples were positive in the qPCR for Bartonella spp. based on the nuoG gene. Seven animals (15.56%) were positive in the nPCR based on the 16S rRNA gene of hemoplasmas. Of these, three were positive in a PCR based on the 23S rRNA gene. The phylogenies based on both 16S rRNA and 23S rRNA genes corroborated to each other and positioned the sequences in the same clade of hemoplasmas previously detected in D. aurita and D. albiventris sampled in Brazil. Finally, three (6.66%) animals were positive in the PCR for Hepatozoon spp.; the obtained 18S rRNA sequence was positioned into the H. felis clade.The present study showed, for the first time, the circulation of piroplasmids, Hepatozoon spp., Ehrlichia spp., hemoplasmas and Bartonella spp. in D. marsupialis sampled in northeastern Brazil, with description of putative novel genotypes of Ehrlichia and Hepatozoon and copositivity by different vector-borne agents. The present work consolidates the South American Marsupialia piroplasmid clade, adding one more genotype of Babesia sp. to this clade.
Keywords: Babesia spp.; Bartonella spp.; Ehrlichia spp.; Hemoplasmas; Hepatozoon spp.; Opossum